(untitled) (Economics and region, 2021)
The pandemic has hampered the continent’s development efforts. Thus, the growth rate in sub-Saharan Africa fell from 2.4% in 2019 to 5.1% in 2020. According to the latest edition of Africa’s Pulse, the World Bank’s semi-annual report on the economic climate in Africa, the region is expected to fall into its first recession in more than 25 years. African leaders are strongly recommended to strengthen health systems and respond quickly and effectively to avoid disruption in food supply chains and the damage that would cause. The authors of the report also recommend setting up safety nets for vulnerable populations and workers in the informal sector. While most African countries are affected to varying degrees by the pandemic, growth in real gross domestic product should, in particular, impact the three largest economies in sub-Saharan Africa (Nigeria, Angola and South Africa). The countries the most affected are those whose exports are composed mainly of raw materials. These are of course the countries commonly called "rentier countries". A review of the literature on Covid-19 reveals other aspects of the crisis that are more relevant to the field of geopolitics; it is about security, migration and terrorism. Combined with other global factors, the assembly of the dimensions mentioned above suggests a new configuration of relations between Africa and the great powers, on one side, and between Africa and emerging countries, on the other. It is important to remember that although at first glance these issues may seem distinct from each other, they should be addressed together as they influence and influence each other. The global epidemic could wreak havoc in fragile states, triggering widespread unrest and put a strain on crisis management systems. Its implications are particularly serious for those caught in the middle of a conflict if the disease disrupts the flow of humanitarian aid, limits peace operations and diverts the parties in conflict from emerging or ongoing diplomatic efforts. A year has passed since the appearance of Covid-19 in Africa, and uncertainty remains the rule. The most seasoned experts are left without opinions when it comes to deciding the future. However, all agree that the fight against the pandemic has been largely aided by the combined action of governments, institutions, academics, businesses, civil society and ordinary citizens. The return to normal will depend in the first place on the perpetuation of this spirit of solidarity even if this remains relatively relative in the face of a multifaceted Africa. The crisis could be the answer to a series of curses that have befallen Africa since the advent of independence. The continent is surprising. In some countries, Covid-19 has shown that another Africa is possible if the response is inclusive in the sense that we take into account the weight of the informal sector. This attempts at "reform of the informal," but gently this time. This is the principle of "soft relativism" dear to supporters of critical thinking. In this spirit, a merciless fight against inequalities is essential.